Pengaruh Gaya Kepemimpinan, Kompensasi, dan Kepuasan Kerja Terhadap Kinerja Anggota Organisasi - Ezra Ikhwandaru; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The research was conducted with the aim of analyzing the relationship between the variables of leadership style, compensation and job satisfaction on the performance of organizational members. This type of research is carried out using quantitative methods accompanied by descriptive analysis. The technique used in collecting data for this research was obtained online using a 1-5 Likert scale questionnaire to 100 respondents with criteria of >15 years and who had worked or participated in a team/organization/company. Data analysis was carried out using external measurement techniques, discriminant validity, reliability value measurement, Cronbach's Alpha and internal measurements by calculating the T test, coefficient of determination, f-square test, and VIF using the SmartPLS application. The purpose of this research is to prove the relationship between 1) leadership style has a positive influence on the performance of organizational members, 2) compensation has a positive influence on the performance of organizational members, 3) job satisfaction has a positive influence on the performance of organizational members.